The Middle Stone Age in the Congo Basin: an historiographical overview - (:unkn) unknown (My University, 2020)
A large part of Africa recently revealed important Middle Stone Age remains arguing for the emergence and spread of Homo sapiens on the African continent as early as the Middle Pleistocene. However, our knowledge of the role of the Congo Basin in continental and regional population dynamics remains misunderstood. The poor preservation of bone remains and chrono-stratigraphic contexts of Pleistocene open-air sites is often considered to be the main obstacles of Stone Age studies in Central Africa. Nearly a century after the creation of the first prehistoric cultural facies in Central Africa, the Tumbakultur, this paper goes through the history of the Congo Basin Middle Stone Age. We suggest that nomenclature, variability of approaches on lithic assemblages, the fragmentation of knowledge and dispersion of prehistoric collections are all factors which must be taken into account in order to develop new perspectives for future Stone Age research program in the Congo Basin.
Keywords: African Research